The Relationship Between Philosophical Logic and Religion - Rizka Naine Putri; Aliya Zavira Parinduri; Siti Syarah; Muhammad Arif Hsb; khairul Fahri (ISNU Nine-Star Multidisciplinary Journal, 2025)
Logic, Philosophy, and Religion. While each has distinct goals and approaches, all three play a crucial role in shaping how humans understand themselves, the world, and the transcendental reality that transcends empirical knowledge. While the relationship between logic, philosophy, and religion is often complex due to their unique characteristics, they often interact with one another in the search for truth. The relationship between logic, philosophy, and religion has been a contentious one throughout the history of human thought. However, they complement each other in addressing complex life issues. While philosophy provides space for critical reflection on religion, logic provides philosophy with the tools to develop stronger arguments. At the same time, religion can enrich both logic and philosophy by providing deeper purpose and value in the search for truth.